On Education & the Common Good - John Covaleskie (Arizona State University, 1994)
This response to Coulson's recent EPAA piece, "Human Life, Human Organizations, and Education," argues that Coulson is wrong about "human nature," social life, and the effects of unregulated capitalist markets. On these grounds, it is argued that his call to remove education from the public sphere should be rejected. The point is that education is certainly beneficial to individuals who receive it, but to think of education as purely a private and personal good properly distributed through the market is seriously to misconstrue the meaning of education. We should not care to be the sort of people who do so.